2016
DOI: 10.1242/dev.139642
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of microRNA-150 in mammary epithelium suppresses secretory activation and impairs de novo lipogenesis

Abstract: Profiling of RNA from mouse mammary epithelial cells (MECs) isolated on pregnancy day (P)14 and lactation day (L)2 revealed that the majority of differentially expressed microRNA declined precipitously between late pregnancy and lactation. The decline in miR-150, which exhibited the greatest fold-decrease, was verified quantitatively and qualitatively. To test the hypothesis that the decline in miR-150 is crucial for lactation, MEC-specific constitutive miR-150 was achieved by crossing ROSA26-lox-STOP-lox-miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…miR-150 was previously reported to play important roles in controlling B cell differentiation by targeting the transcription factor c-Myb (28). Moreover, miR-150 has been reported to regulate de novo lipogenesis by targeting Fasn and other lipid-related genes in mammary epithelium (29). Here, we uncover a potentially novel role for miR-150 in macrophages to regulate cholesterol metabolism and lipid trafficking genes involved in AMD based on our RNA-Seq results.…”
Section: Discussionmentioning
confidence: 57%
“…miR-150 was previously reported to play important roles in controlling B cell differentiation by targeting the transcription factor c-Myb (28). Moreover, miR-150 has been reported to regulate de novo lipogenesis by targeting Fasn and other lipid-related genes in mammary epithelium (29). Here, we uncover a potentially novel role for miR-150 in macrophages to regulate cholesterol metabolism and lipid trafficking genes involved in AMD based on our RNA-Seq results.…”
Section: Discussionmentioning
confidence: 57%
“…We also checked expression of miR-134, miR-150-5p and miR-200a, which reportedly regulate STAT5b expression [30][31][32] in X-ray irradiation HeLa cells. The expression of miR-34a, who is up-regulated after irradiation [14], was used as a reference of radiation treatment.…”
Section: Ionizing Radiation-induced Mir-5094 Expression Results In Stmentioning
confidence: 99%
“…It was reported that miR-200a directly repressed STAT5b expression in both mice and human [30], while miR-134 was showed to inhibit proliferation, survival and xenograft growth in cancer cell and stem-cell by targeting STAT5b and KRAS [31]. Similarly, miR-150 was demonstrated to suppress expression of STAT5b in mammary epithelial cells of bitransgenic mice [32]. Whether and how miRNAs regulate STAT5b in DNA damage response to IR remains to be an open question.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Additionally, the previous studies offered us reliable experimental buttress to the prediction in our ceRNA network. The FASN-3'-UTRluciferase assay was successfully performed to validate the ability of miR-150-5p to target FASN in the mice experiment 52 . MiR-21 was able to induce the tumor growth by targeting TGFBI in non-small cell lung cancer cells 53 and pancreatic cancer cells 54 , demonstrating the relative stability of our predictions though experimental investigation in BLCA is demanded.…”
Section: Discussionmentioning
confidence: 99%